2017
DOI: 10.1177/1049731517729039
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Youth Mental Health First Aid USA for Social Work Students

Abstract: Purpose: Adolescent mental health is a public health priority. Considered an early intervention approach, Youth Mental Health First Aid (YMHFA) trains adults to provide initial assistance to adolescents experiencing a mental health problem or crisis. This study evaluated the effectiveness of the U.S. version of YMHFA (YMHFA-USA) among graduate social work students. Method: A quasi-experimental design ( N = 73; intervention, n = 39; comparison, n = 34), using the Mental Health Beliefs and Literacy Scale, assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Sixteen studies were excluded at the full-text screening stage: 11 were not an MHFA program, 4 were not an RCT or controlled trial, and 1 was a duplicate publication. A final 18 studies were included in the review, with a total of 5936 participants [ 13 22 , 42 49 ]. Only 6 of these were included in the prior review of MHFA [ 13 , 17 19 , 45 , 48 ], with 12 additional controlled trials identified.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies were excluded at the full-text screening stage: 11 were not an MHFA program, 4 were not an RCT or controlled trial, and 1 was a duplicate publication. A final 18 studies were included in the review, with a total of 5936 participants [ 13 22 , 42 49 ]. Only 6 of these were included in the prior review of MHFA [ 13 , 17 19 , 45 , 48 ], with 12 additional controlled trials identified.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation studies of the YMHFA program, however, have indicated that improving mental health literacy is insufficient for increasing appropriate helping behaviors in the real world. Although previous evaluation studies of the YMHFA reported improvements in confidence in offering help [25,33], understanding of the five steps of helping behaviors [31], and recognizing the importance of offering help [32], they did not show that the programs significantly increased the numbers of actual helping behaviors. Why was the existing YMHFA program not able to effectively increase appropriate helping behaviors?…”
mentioning
confidence: 80%
“…This 14-h program can be conducted as either over two full days or four small sessions, and those instructors registered on the MHFA website [30] teach how to recognize and help young people with mental disorders and facilitate role plays between participants to develop practical skills of helping behavior (for more details, see [25]). An evaluation study of the YMHFA in Australia has demonstrated improvements in knowledge of mental disorders, stigmatizing attitudes, and confidence in offering help [25], and this program has been conducted in the United States [31][32][33]. To improve literacy regarding the worldwide problem of depression among youth, it is hoped that the YMHFA will be used globally in future, as well as the original MHFA that has already been conducted and evaluated in over 22 countries [34], including the United Kingdom [35,36], the United States [37], and Japan [38][39][40].…”
mentioning
confidence: 99%
“…One of the studies (Pereira et al, 2015) reported that their waitlist control group had a lower rating compared to one of the training groups post‐training. One study did not report data due to unacceptable reliability (Rose et al, 2017). Effect sizes ranged from 0.36 to 1.18 at post‐training (n = 9) and 0.68 to 1.0 at follow‐up (n = 2).…”
Section: Resultsmentioning
confidence: 99%